Imagem organizacional pública: um estudo teórico e empírico utilizando Inteligência Artificial desenvolvido no Triângulo Mineiro - Silveira, Carolina Coelho da (2024)
Context: Following a trend already observed in the private sector, organizational image has become one of the concepts of greatest interest for public organizations, gaining strategic value. However, the topic is still in its early stages, and applicable methodological procedures show little diversity. Objective: The main objective of this research was to develop a tool, based on Artificial Intelligence techniques, capable of capturing the organizational image of public entities in the Triângulo Mineiro and Alto Paranaíba regions as constructed by the national press, focusing on news portals and newspapers. Method: This dissertation consists of two articles: the first adopts a qualitative approach, translated into a narrative literature review on the theme of public organizational image, considering the context of State Reform and modernization of the Brazilian Public Administration. The second article is theoretical-empirical, and through Text Mining and Natural Language Processing techniques, 1.570 news articles about the studied organization published between jan/2022 and sep/2023 were analyzed to diagnose the organizational image. Results: The first article resulted in a necessary update and consolidation of the organizational image concept, contributing to the understanding of the theme in a less- explored context. The results of the second article indicate the concentration of news about the studied organization in some press outlets; the existence of peaks in coverage; that the most frequently associated adjectives with the organization do not have a negative tone; and a list of main related topics. Research Relevance to the PPGADM Concentration Area and Research Line: For the development of this research, the case of the Municipal Department of Water and Sewage (DMAE) of the Municipality of Uberlândia was used to promote cooperation between academic, institutional, and social spheres for regional development. Impact and Innovative Character in Intellectual Production: This study promotes methodological renewal and innovation in data analysis techniques, going beyond traditional practices usually used in previous studies on the subject. Economic, Social, and Regional Impact: The results of this study bring contributions to practice translated into the development of management tools for public organizations. The developed tool produces inputs that allow organizations to guide communication actions and make decisions on a range of issues that contribute to the development of the organization, improvement of services, and increased citizen satisfaction. Regional Implications: It contributed to advancing the integration of Artificial Intelligence in the public sphere and the adoption of innovative tools; consequently, it can contribute to the leadership, strategy, and control implemented to assess, guide, and monitor the performance of regional public management, aiming at the implementation of public policies and the provision of services of interest to society. Sustainable Development Goals Addressed in the Research: This research aligns with SDG 16 – Peace, Justice, and Strong Institutions, contributing to Goals 16.6 and 16.7.